FOREIGN EXPERIENCE OF PROVIDING STATE PROTECTION OF INTELLECTUAL PROPERTY - Fesenko N.S., (Pressing Problems of Public Administration, 2016)
The paper describes the evolution of the legal support for intellectual property rights throughoutthe world. Stages of building a system of international law protecting intellectual sector productswere analyzed, from the first conventions to evaluation of activities of the World Intellectual PropertyOrganization and the International Intellectual Property Alliance. The need to harmonize the relevantlaws of Ukraine with its Budget Code, to implement the EU regulatory standards in the nationallegislation, and to make amendments to special laws in the field of intellectual property protectionhas been justi ed.